Effects of methyldopa on vegf levels as proangiogenic factor in severe pre-eclampsia at haji hospital, surabaya - Juwita, Dina Ratna; Yulistiani, Yulistiani; M, Eddy Zarkaty (Folia Medica Indonesiana, 2017)
Methyldopa is the main antihypertensive drug widely used in pregnant women with hypertensive disorder. It lowers blood pressure in pre-eclampsia by affecting a2-adrenoreceptors in central nervous system. However, it also decreases the production of proangio-genic factors that involved in the pathophysiology of hypertension in pre-eclampsia. Vascular Endothelial Growth Factor (VEGF) is one of proangiogenic and mitogenic factor that important for vasodilatation. VEGF is produced by the placenta and affected after treatment with methyldopa. The aim of this study was to analyze the effects of methyldopa on VEGF maternal circulating level as a proangiogenic factor in severe pre-eclampsia patients who were hospitalized at Obstetrics and Gynecology Department, Haji Hospital, Surabaya. This study was performed by cohort prospective observational method on August to October 2016.The data was assessed at before and 48 hours after methyldopa therapy. The study was approved by the ethical committee of Haji Hospital, Surabaya. There were 19 patients with severe pre-eclampsia who met inclusive criteria. The results showed that levels of VEGF before and 48 hours after 250 mg methyldopa therapy were 1178.37(281.97-3567.28) pg/mL and 1055.17 (129.79-4272.66) pg/mL, respectively. VEGF levels in severe pre-eclampsia patients were 1194.29 (175.68-3432.01) pg/mL at before treatment and 510.66 (214.34-1236.16) pg/mL after treatment with methyldopa 500 mg therapy. In conclusion, methyldopa could decrease VEGF level on severe pre-eclampsia patients, with a decrease of 10% at the dose of 250 mg and 57% at the dose of 500 mg.